Job Search Monitoring and Unemployment Duration in Hungary: Evidence from a Randomised Control Trial - John Micklewright; Gyula Nagy (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2005)
The impact of the administration of unemployment benefits on time spent unemployed is a neglected issue in discussion of incentive effects in Central and Eastern Europe. We use Labour Force Survey data, ad-ministrative registers and inspection of benefit office practices to show that there is good reason to investigate this issue in Hungary. We then report on results from a field experiment of the impact of tightening the administration of benefits in which benefit claimants were randomly as-signed to treatment and control groups. Treatment has quite a large ef-fect on durations on benefit of women aged 30 and over while we find no effect for younger women or for men.
Keywords: J64; J65; P23; 330; experiment; job search; unemployment insurance; Hungary; Arbeitslosenversicherung; Langzeitarbeitslosigkeit; Arbeitsuche; Wirkungsanalyse; Ungarn